Prospective Observational Evaluation of Sedation and Pain Management Guideline Adherence Across New Jersey Intensive Care Units. (October 2019) - Brophy, Alison; Cardinale, Maria; Andrews, Liza B.; Kaplan, Justin B.; Adams, Christopher; Opsha, Yekaterina; Brandt, Kimberly A.; Dixit, Deepali; Nerenberg, Steven F.; Saleh, Julie A.
Background: The practice guidelines for the management of pain, agitation, and delirium (PAD) from the Society of Critical Care Medicine shifted from primarily focusing on the treatment of anxiety in 2002 to the treatment of pain in 2013. Objective: This prospective, observational, multicenter study aimed to assess the degree of practice adherence to the PAD guidelines for ventilated patients in New Jersey intensive care units (ICUs). Methods: Pharmacist investigators at 8 centers designated 4 days at least 10 days apart to evaluate all patients on mechanical ventilation. The primary outcomes included adherence to 4 guideline recommendations: treatment of pain before sedation, use of nonnarcotic analgesic medications, use of nonbenzodiazepine sedative medications, and use of goal-directed sedation. Results: Of 138 patients evaluated, 50% had a primary medical diagnosis (as opposed to surgical, cardiac, or neurological diagnosis), and the median Sequential Organ Failure Assessment (SOFA) score was 7. Pain was treated prior to administration of sedatives in 55.4% of subjects, with fentanyl being the primary analgesic used. In addition, 19% received no analgesia, and 11.5% received nonopioid analgesia. Sedative agents were administered to 87 subjects (48 nonbenzodiazepine and 39 benzodiazepine). Of those receiving benzodiazepines, 22 received intermittent bolus regimens and 16 received continuous infusions, of which 5 were for another indication besides sedation. Validated scales measuring the degree of sedation were completed at least once in 56 (81.6%) patients receiving sedatives. Conclusions: Current sedation practices suggest that integration of evidence-based PAD guidelines across New Jersey adult ICUs is inconsistent despite pharmacist involvement.